Diversidade genética de isolados de Thielaviopsis paradoxa em cana-de-açúcar - Medeiros, Carolina de Cássia Pani [UNESP] (2015)
Once mechanization allows sugarcane planting in almost all year and increases mechanical injuries, this type of planting provides the occurrence of many diseases, as pineapple disease, which is an economically important sugarcane disease that occurs in almost all sugarcane commercial planting areas. The genetic improvement of sugarcane to this disease is affected because of the lack of studies about genetic diversity of Thielaviopsis paradoxa, causal agent of pineapple disease. Thus, the genetic diversity study of 11 isolates of T. paradoxa from five different sugarcane commercial planting areas was accomplished using AFLP technique. A total of 298 polymorphic bands were obtained, but only 174 polymorphic bands had correlation different than (1) or (-1) in the 11 isolates of T. paradoxa. Based on our result was possible to infer genetic variation among T. paradoxa isolates. Once T. paradoxa is parasitic on a range of economic and food crops, this fact can explain the detected genetic variation among T. paradoxa isolates. The medium values of PIC (Polymorphism Information Content) of each primers combination revealed an average of 0,406, which can be considered high (informative), once the molecular marker is dominant. The phenogram, obtained by 174 polymorphic bands, separated the 11 isolates in three different groups. The group I contained five isolates and three Brazilian States (BA, GO e SP), the group II contained five isolates and three Brazilian States (SP, PR e MG) and the group III contained only one isolate and one Brazilian State (SP). Therefore, this study showed high polymorphism among T. paradoxa isolates, what reveal high genetic variability in this phytopathogenic specie